STUDY ON WASTE wATERS OF METAL FINISHING INDUSTRIES AROUND LAHORE METROPOLITAN AREA - Roston, G D (Biological Sciences - PJSIR, 2002)
Study was undertaken on the wastewater samples from metal finishing industries of Lahore metropolitan area for the evaluation of metallic impurities. The metal finishing industry was classified into three categories i.e. medium scale, small scale and cottage scale industry. About 93 wastewater samples were collected from various metal finishing industries around Lahore metropolitan area. In addition to toxic elements like cadmium, nickel and zinc the other parameters such as hydrogen ion concentration (pH), Electrical Conductivity (EC) and Total Dissolved Salts (TDS) were also determined.